Efeitos da cafeína na cognição humana: motivações para o consumo e efeitos agudos em processos atencionais e domínios executivos - Mariano, Juliana Lanini [UNIFESP] (2014)
Caffeine is the most consumed psychostimulant in the world, but the motivations related to its use are unclear. Previous studies have shown that acute caffeine consumption exerts beneficial effects on subjective feelings of arousal, as well as on simple and sustained attentional processes. Moreover, although caffeine-containing products are often consumed with a glucose source, which also has cognitive effects, very few studies have investigated their integrated effects on cognitive functioning, specially taking into account more complex attentional processes (executive functioning). To address these issues, we investigated the motivations for caffeine consumption and whether arousal and cognitive enhancing effects were among these motivations (study 1) and also the effects of acute doses of caffeine ranging from habitual personalized doses (“basal” doses) to challenge doses (basal + 150 or basal + 300 mg) on attentional/executive measures (study 2). To investigate motivation for caffeine consumption we used an online questionnaire responded by a University sample of 965 people. Motivations for caffeine use were grouped into factors with an exploratory factor analysis followed by a structural model to investigate which factors were related to caffeine consumption. To investigate acute caffeine-effects we ran a double-blind, placebo-controlled study including young, healthy, rested, male habitual caffeine consumers. In order to investigate the effects of basal doses and its interaction with food (Study 2A, n=60) subjects were randomly assigned to one of 4 treatments: fastingplacebo, fasting-caffeine, meal-placebo, meal-caffeine. To investigate the effects of challenge doses of caffeine (Study 2B, n=60) subjects were randomly assigned to one of 4 treatments: placebo, basal, basal+150 and basal+300. Caffeine habitual doses were individualized for each participant based on their self-reported caffeine consumption at the time of testing. The test battery included measures of simple and sustained attention, executive domains (inhibition, updating, shifting, dual-tasking, planning, access to long-term memory, and metacognition), control measures of subjective alterations, glucose and insulin levels, skin conductance, heart rate and pupil dilation. In study 1, we found that the main predictors for caffeine use are related to its stimulant properties (alertness improvement) and to the pleasure associated to its consumption (social reasons and preference for the taste of caffeinated products). Study 2A showed that regardless of meal intake, acute habitual doses of caffeine 193 significantly improved simple and sustained attention and decreased subjective symptoms of fatigue. Updating was the only executive domain sensitive to caffeineinduced enhancement. Pupil size during the task that indexed updating also indicated use of less cognitive effort. In study 2B we found no dose-dependent effects. In conclusion, the participants’ morning caffeine “fix” had positive attentional effects and selectively improved executive updating irrespective of the presence of food, but increasing this dose did not lead to better effects. These findings are in agreement with the motivations for caffeine use and indicate that habitual caffeine consumers can adjust, by everyday usage, the ideal amount of caffeine to achieve these goals.